2000
DOI: 10.1093/geronb/55.2.s117
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Functional Health Status of Older Women With Heart Disease: Evaluation of a Program Based on Self-Regulation

Abstract: A self-regulation-based program that was provided to older women with heart disease and that focused on physical activity and disease management problems salient to them, improved their physical functioning and symptom experience. Psychosocial benefit was not evident and may be a result of measurement error or due to insufficient program time spent on psychosocial aspects of functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 45 publications
1
55
0
Order By: Relevance
“…The outcomes of program evaluation have been reported elsewhere. 12, 13 The "Women Take PRIDE"program differs from traditional Phase II cardiac rehabilitation in that program participants report a range of cardiac diagnoses in addition to coronary artery disease and are not enrolled as a result of an acute event. The emphasis is on the long-term management of the heart condition.…”
Section: Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcomes of program evaluation have been reported elsewhere. 12, 13 The "Women Take PRIDE"program differs from traditional Phase II cardiac rehabilitation in that program participants report a range of cardiac diagnoses in addition to coronary artery disease and are not enrolled as a result of an acute event. The emphasis is on the long-term management of the heart condition.…”
Section: Interventionmentioning
confidence: 99%
“…11 At 12 months follow-up, women in the program, compared with controls, were less symptomatic (P Ͻ0.01), scored better on the physical dimension of the Sickness Impact Profile (P Ͻ0.01), demonstrated improved ambulation as measured by the 6-minute walk test (P ϭ 0.01), and lost more body weight (P Ͻ0.001). 12, 13 The specific aims of the study include: assessing the impact of the WTP heart disease selfmanagement program on the use of hospital services by older women; determining the approximate hospital cost savings attributed to older women who participated in the program; and comparing potential cost savings with the costs of operating the disease self-management program.…”
mentioning
confidence: 99%
“…Previous studies have shown that similar health behavior changes, when sustained, continue to positively impact health and reduce utilization of health care services (Clark et al, 2000;Wagner et al, 2001). Based on the results of clinical trials of CDSMP, the successful implementation of the program in South Florida can be expected to improve quality of life for older adult residents (Lorig et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Data on physical and psychosocial function, as well as cardiac symptom experience were collected by telephone survey at baseline, 4-months, and 12-months. (Clark et al, 2000) Local implementation of WTP. The community demonstration of the WTP program reported here was implemented by a partnership of five organizations in New York's capital region.…”
Section: Methodsmentioning
confidence: 99%